Keputusan Inggris Menetapkan Kepulauan Chagos sebagai Marine Protected Area (MPA) - Ary Trisna, Ni Nyoman; Dharmiasih, D.A. Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT The Chagos Archipelago is one of the British territories in the Indian Ocean and play a role in safeguarding the security interests of Britain in the region. The British government in safeguarding its security interests in the Chagos Islands has designated the archipelago as a no-take Marine Protected Area (MPA). This was done to safeguard the security interests of a joint military bases between Britain and the United States. The military base is located on one of the islands in the Chagos Islands named Diego Garcia. Britain's decision to establish the Chagos Archipelago as a no-take MPA was taken after protests from indigenous people of the Chagos Islands and Mauritius who wanted to return to their territory. This study analyzes the security interests of British in protecting its military bases by implementing environmental policies. The Theoritical Framework used in this study is National Security and Military-Environmentalism. Keywords: Marine Protected Area, military base, national security, military environmentalism